Analysis of fatty acids in ghee and olive oil and their probable causal effect in lipoid pneumonia - Mirghani Zein; Zein Tayseer; Annoble Samuel; Winter John; Mostafa Randa (Journal of Medical Biochemistry, 2011)
Lipoid pneumonia develops when lipids enter the bronchial tree. This form of pneumonia is common in some developing countries where it is a traditional practice to give infants oily products (ghee and olive oil) for various reasons. We have analyzed and identified the fatty acids found in homemade ghee and in olive oil and compared them to fatty acids found in bronchoalveolar lavage of children with lipoid pneumonia. The three fatty acids common to homemade ghee, olive oil and bronchoalveolar lavage are linoleic, oleic, and stearic. The rest of the fatty acids, namely, lauric, myristoleic, myristic, pentadecenoic, pentadecanoic, heptadecenoic and heptadecanoic are found either in homemade ghee and/or olive oil but not in bronchoalveolar lavage. Therefore the deleterious effects to the lung parenchyma found in lipoid pneumonia are probably caused by these three fatty acids. Further investigations are required to ascertain the effects of the individual fatty acids found in homemade ghee and olive oil. .